The mediation effect of social participation in the relationship between Internet use and health behaviors among middle-aged and older individuals - Xinmei Yang; Yang Chen; Tuo Qiu; Xingyue Zhu (Digital Health)
Objectives The increasing popularity and influence of the Internet in modern society have greatly impacted individuals’ lives. This population-based study elucidated the dynamic linkage between Internet use (IU) and health behaviors (HBs), particularly emphasizing the intermediary function of social participation (SP) in middle-aged and older adults (MOA) in China. Methods Data were obtained from the China Health and Retirement Longitudinal Study in 2020. This study employed binary logistic regression to investigate the influence of IU on the HBs of MOA in China. Additionally, binary logistic and multiple linear regressions were used to test whether SP regulates the relationship between IU and HBs (i.e. nonsmoking, non-drinking, physical activity, and physical examination). Furthermore, the Karlson-Holm-Breen method was employed to assess the mediating role of SP. Results IU had a positive effect on nonsmoking (OR: 1.113, p  < 0.05), physical activity (OR: 1.775, p  < 0.001), and physical examination (OR: 1.226, p  < 0.001). However, this study revealed that IU had a significant negative effect on non-drinking (OR: 0.775, p  < 0.001). Moreover, the mediating effect analysis demonstrated that SP played a mediating role in the relationship between IU and the HBs. Conclusion Active engagement in social activities is an effective method for enhancing the positive impact of IU on the adoption of physical activity and physical examinations. In order to meet individuals’ needs, it is essential to design and promote Internet health services and social activities tailored to their age group and cultural background. Furthermore, greater efforts should be employed to implement public policy initiatives aimed at providing care for MOA.